Electroacupuncture Reduces the Effects of Acute Noxious Stimulation on the Electrical Activity of Pain-Related Neurons in the Hippocampus of Control and Neuropathic Pain Rats - Jun-Ying Wang; Renbo Chen; Shu-Ping Chen; Yong-Hui Gao; Jian-Liang Zhang; Xiu-Mei Feng; Yaxia Yan; Jun-Ling Liu; Ingrid Gaischek; Daniela Litscher; Lu Wang; Irmgard Th. Lippe; et al. (Neural Plasticity)
To study the effects of acupuncture analgesia on the hippocampus, we observed the effects of electroacupuncture (EA) and mitogen-activated protein kinase (MEK) inhibitor on pain-excited neurons (PENs) and pain-inhibited neurons (PINs) in the hippocampal area CA1 of sham or chronic constrictive injury (CCI) rats. The animals were randomly divided into a control, a CCI, and a U0126 (MEK1/2 inhibitor) group. In all experiments, we briefly (10-second duration) stimulated the sciatic nerve electrically and recorded the firing rates of PENs and PINs. The results showed that in both sham and CCI rats brief sciatic nerve stimulation significantly increased the electrical activity of PENs and markedly decreased the electrical activity of PINs. These effects were significantly greater in CCI rats compared to sham rats. EA treatment reduced the effects of the noxious stimulus on PENs and PINs in both sham and CCI rats. The effects of EA treatment could be inhibited by U0126 in sham-operated rats. The results suggest that EA reduces effects of acute sciatic nerve stimulation on PENs and PINs in the CA1 region of the hippocampus of both sham and CCI rats and that the ERK (extracellular regulated kinase) signaling pathway is involved in the modulation of EA analgesia.